History wars : the Enola Gay and other battles for the American past - Linenthal, Edward Tabor 1947-; Engelhardt, Tom 1944- (Henry Holt and Company, 1996)
From the Òtaming of the WestÓ to the dropping of the atomic bomb on Hiroshima, the portrayal of the past has become a battleground at the heart of American politics. What kind of history Americans should read, see, or fund is no longer merely a matter of professional interest to teachers, historians, and museum curators. Everywhere now, history is increasingly being held hostage, but to what end and why? InHistory Wars, eight prominent historians consider the angry swirl of emotions that now surrounds public memory. Included are trenchant essays by Paul Boyer, John W. Dower, Tom Engelhardt, Richard H. Kohn, Edward Linenthal, Micahel S. Sherry, Marilyn B. Young, and Mike Wallace.